Implementasi Hadis-hadis Puritan Kitab Bulugh al-Maram Berbasis Moderasi Beragama di Pesantren Mambaul Ulum Mojokerto - Moh. Misbakhul Khoir (Refleksi: Jurnal Kajian Agama dan Filsafat, 2023)
Puritanical, fundamental, radical and intolerant religious understanding can trigger acts of violence in the form of terrorism. The countermeasure that can be done is to instill moderation values in understanding and practicing religious teachings. One of the important means in instilling religious moderation values is through Islamic education, especially pesantren-based education. Therefore, examining the strategic steps of pesantren in instilling moderation is important to do, especially when dealing with puritanical texts. This study aims to find out the understanding, implementation and cultivation of religious moderation values of puritanical Hadiths in pesantren. This research was designed qualitatively by using observation, interview and documentation instruments to obtain the required data. The results of this study state that in understanding puritanical Hadith on the issue of hudud, pesantrens tend to be textualist, as a form of caution on Allah's law. While its implementation is moderate, showing a wise attitude as a result of the breadth of the pesantren’s scientific insight. Meanwhile, the cultivation of religious moderation values is carried out with a habituation learning model, as an effective way and in accordance with the conditions of the pesantren.